ANALYSIS OF EFFECT OF SPEED SPEED AND PHYSICAL EXPERIENCE ON PAINTING TEMPERATURE ON LATHE MACHINE - Didik Nurhadiyanto (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2002)
The propose of this experiment was to analyze the effect of feedingspeed and cutting depth that effecting cutter temperature. The scatter diagram and variant analysis was used to analyze the data of thisexperiment. The analysis shows that both feeding speed and cutting depth were influencing cutter temperature. The effect of interaction between feeding speed and cutting depth were influencing cutter temperature.